Gender Inequality and Power Imbalance in Taylor Swift’s Songs “Dear John” and “All Too Well” - Imtiyaz, Rana; Ramadhina, Retno; Priyoto, priyoto (STIBA IEC JAKARTA, 2025)
This study looks at how gender inequality and power imbalances in romantic relationships are shown in Taylor Swift's songs